Socrates on trial : a play based on Aristophanes' Clouds and Plato's Apology, Crito, and Phaedo, adapted for modern performance - Irvine, A. D. (University of Toronto Press, 2008)
"More than 2,400 years after his death, Socrates remains an iconic but controversial figure. To his followers, he personified progressive Greek ideals of justice and wisdom. To his detractors, he was a corruptor of the young during wartime and one of the reasons Athens suffered its humiliating defeat at the hands of Sparta in 404 BC. Socrates' story is one of historic proportions and his unyielding pursuit of truth remains controversial and relevant to the present day." "Socrates on Trial presents the story of Socrates as told to us by Aristophaues, Plato, Xenophon, and others. The play uses fresh language to emphasize what is important in the works of these ancient authors, while at the same time remaining faithful to the general tenor and tone of their writings. Andrew Irvine has created a script that not only fits comfortably into the space of a single theatrical performance, but is also informative and entertaining. Suited for informal dramatic readings as well as regular theatrical performances, Socrates on Trial will undoubtedly appeal to instructors and students alike."--Jacket